Pengembangan Media Pembelajaran Interaktif Berbantuan Articulate Storyline pada Materi Rasio untuk Siswa Kelas VII - Ramdanah, Saima; Karim, Karim; Noorbaiti, Rahmita (Mandalika Mathematics and Educations Journal, 2025)
The rapid advancement of technology poses challenges for educators to innovate in improving the quality of learning in the classroom. In addition, students grow up in an environment that is familiar with technology, so learning needs to be integrated with technology to suit their needs better. This research aims to develop interactive learning media assisted by Articulate Storyline on ratio material for seventh-grade students that meet the criteria of valid, practical, and effective. This research uses the Research and Development (R&D) research method with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The results showed: (1) the learning media is categorized as very valid based on the results of material validation which reached a percentage of 91.25% and media validation of 93.75%, (2) the learning media is declared very practical because the response questionnaire of students and teachers reached a percentage of 88.89% and 83.33%, respectively, and (3) the learning media is in the medium or effective category because the N-gain test results show an average N-gain of 0.65. Thus, this interactive learning media of Articulate Storyline-assisted ratio can be declared valid, practical, and effective.